Applications of nanocomposites based on zeolitic imidazolate framework-8 in photodynamic and synergistic anti-tumor therapy. Issue 26 (9th June 2022) - Kang, Wen; Tian, Ying; Zhao, Ying; Yin, Xindao; Teng, Zhaogang
Abstract : In this paper, the synthesis mechanism of ZIF-8 nanoplatform and its application in photodynamic therapy and synergistic therapy are reviewed. Abstract : Due to the limitations resulting from hypoxia and the self-aggregation of photosensitizers, photodynamic therapy (PDT) has not been applied clinically to treat most types of solid tumors. Zeolitic imidazolate framework-8 (ZIF-8) is a common metal–organic framework that has ultra-high porosity, an adjustable structure, good biocompatibility, and pH-induced biodegradability. In this review, we summarize the applications of ZIF-8 and its derivatives in PDT. This review is divided into two parts. In the first part, we summarize progress in the application of ZIF-8 to enhance PDT and realize theranostics. We discuss the use of ZIF-8 to avoid the self-aggregation of photosensitizers, alleviate hypoxia, increase the PDT penetration depth, and combine PDT with multi-modal imaging. In the second part, we summarize how ZIF-8 can achieve synergistic PDT with other anti-tumor therapies, including chemotherapy, photothermal therapy, chemodynamic therapy, starvation therapy, protein therapy, gene therapy, and immunotherapy. Finally, we highlight the challenges that must be overcome for ZIF-8 to be widely applied in PDT. To the best of our knowledge, this is the first review of ZIF-8-based nanoplatforms for PDT.